Hubungan Pengetahuan Ibu Tentang MP-ASI, Riwayat ASI Eksklusif dan Asupan Makan terhadap Status Gizi pada Balita Usia 1-5 Tahun di Desa Klampok - Puspa Mulyaningrum; Anggray Duvita Wahyani; Diah Ratnasari (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aims to determine the relationship between MP-ASI knowledge and undernourished status, the relationship between exclusive breastfeeding history and undernourished status, and the relationship between food intake and undernourished status. This study uses analytical observational research. The method used is survey and observational using a cross sectional approach, namely the researcher takes data on free variables and bound variables in the same time period. The research was conducted from March to May 2024. The place of research was carried out at the Posyandu of Klampok Village, Wanasari District, Brebes Regency. The population in this study is all mothers who have toddlers in Klampok Village, Wanasari District, Brebes Regency aged 1-5 years which totals 122 toddlers. The sample in this study was malnutrition in 13 Posyandu Klampok Village, Wanasari District, Brebes Regency with a purposive sampling technique, namely a sampling technique with certain considerations. The research sample was collected from 13 Posyandu in the object of the study, resulting in the prevalence of undernutrition status of 122 children under five in Klampok Village, Wanasari District, Brebes Regency in 2024 with an average Z score of -3 to <-2 elementary school. The results showed that there was no relationship between maternal knowledge and nutritional status in toddlers aged 1-5 years with a ρ-value of 0.75, there was no relationship between the history of exclusive breastfeeding of toddlers and nutritional status in toddlers aged 1-5 years with a ρ-value of 0.80 and there was a relationship between toddlers' food intake and malnutrition status in toddlers aged 1-5 years with a ρ-value of 0.028.